Minang Identity in Indonesian Literary Works 2008-2025 (Anthropocentrism Study) - Retnosari, Putri; Parmin; Susanto, Moh Arif; Aditama , Destynar; Rengganis, Ririe; Savitri, Agusniar Dian; Indrawati, Dianita; Faisal , Rakmat; Wibowo, Yermia Nugroho Agung (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to explore the construction and transformation of Minangkabau identity in Indonesian literary works published between 2008 and 2025. Using an anthroposentric literary approach, the research investigates how human-centered cultural values, norms, and beliefs associated with Minangkabau ethnicity are narrated, challenged, or maintained in contemporary fiction. The analysis focuses on selected novels and short stories written by both Minangkabau and non-Minangkabau authors, identifying recurring themes such as adat, migration, gender roles, and intergenerational conflict. The method combines textual interpretation with cultural contextualization to uncover how literature reflects or reconfigures the image of Minang identity in response to changing national and global contexts. The results reveal that while many works reaffirm traditional Minangkabau values, others offer critical perspectives that depict internal tensions and evolving identities, especially among younger generations. The study shows that Minang identity in literature is dynamic, marked by a constant negotiation between heritage and modernity.